Volume 3: Controls, Diagnostics and Instrumentation; Education; Electric Power; Microturbines and Small Turbomachinery; Solar B 2011
DOI: 10.1115/gt2011-46753
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Flow Structures and Losses in a Radial Turbine Nozzle

Abstract: An analysis of secondary flow structures and losses in a variable-vane radial turbine geometry is provided based on CFD. A complete turbine stage of a commercial vehicle turbocharger is modeled, including the entire 360° rotor and stator, in order to account for the circumferential non-uniformity of the flow. The full-stage model consists of approximately 12,500,000 nodes. The stator domain accounts for the endwall clearance on the hub side of the nozzle vanes. As an additional feature typical for variable tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The work of Roumeas and Cros [3] also indicated that the clearance leakage leads to the development of vortices along the nozzle vane chord that tends to increase the total pressure loss in the nozzle. Natkaniec et al [11] performed a numerical research of secondary flow structures and losses in a turbine with realistic vanes and found that some typical vortices generate a lot of flow loss in stator. A two-dimensional nozzle vane generates a straight wake in the downstream region of trailing edge.…”
Section: Shock Wave In Turbinementioning
confidence: 99%
“…The work of Roumeas and Cros [3] also indicated that the clearance leakage leads to the development of vortices along the nozzle vane chord that tends to increase the total pressure loss in the nozzle. Natkaniec et al [11] performed a numerical research of secondary flow structures and losses in a turbine with realistic vanes and found that some typical vortices generate a lot of flow loss in stator. A two-dimensional nozzle vane generates a straight wake in the downstream region of trailing edge.…”
Section: Shock Wave In Turbinementioning
confidence: 99%
“…The stator loss accounts for about 9.8% of overall turbine stage loss, and it could be up to 14.8% considering the spacer. Detailed loss analyses in stator could be found in Putra and Joos, 32 Natkaniec et al 33 and Simpson et al 34 The accumulation of loss in the mainstream passage at the designed condition is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 93%
“…The local peak of the total pressure loss coefficient, which is associated with the inflow vortex and corner vortex, appears at the stator suction side. Some full-stage numerical simulations 33,34 also successfully captured the horse shoe vortices, inflow vortices and corner vortices. The stator loss accounts for about 9.8% of overall turbine stage loss, and it could be up to 14.8% considering the spacer.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, helicity was introduced to discern the secondary flow vortex and study the flow field in the vane. The helicity is the scalar product of the vorticity vector and the velocity of flow, which is also used by Torre [18], Anker [19] and Natkaniec [20] in their study to analyze the complex flow field caused by the secondary flow. In order to understand the evolution of secondary flow vortex in the passage, contours of helicity and isolines of stagnation pressure recovery coefficient are showed in a set of cross section, which locate at 5% C x upstream of the blade leading edge, 30%, 60%, 90% and 120% downstream of the blade leading edge successively.…”
Section: Analysis Of Numerical Resultsmentioning
confidence: 98%